2022
DOI: 10.1109/taffc.2020.3008693
|View full text |Cite
|
Sign up to set email alerts
|

Conveying Emotions Through Device-Initiated Touch

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 76 publications
2
18
0
Order By: Relevance
“…While measuring motion energy is quantitative and informative, we have shown that more detailed physical measurements can further discriminate specific touch messages, e.g., happiness and attention had similar normal velocities but very different tangential velocities, while contact duration and area discriminated love and calming, which had similar tangential velocities. This is consistent with studies of human-delivered touch to pressure sensor surfaces (Gaus et al, 2015;Supratman et al, 2020) and robot-delivered touch to humans (Teyssier et al, 2020) showing that a variety of contact area and motion dynamics measures are required to distinguish different touch actions.…”
Section: Discussionsupporting
confidence: 87%
“…While measuring motion energy is quantitative and informative, we have shown that more detailed physical measurements can further discriminate specific touch messages, e.g., happiness and attention had similar normal velocities but very different tangential velocities, while contact duration and area discriminated love and calming, which had similar tangential velocities. This is consistent with studies of human-delivered touch to pressure sensor surfaces (Gaus et al, 2015;Supratman et al, 2020) and robot-delivered touch to humans (Teyssier et al, 2020) showing that a variety of contact area and motion dynamics measures are required to distinguish different touch actions.…”
Section: Discussionsupporting
confidence: 87%
“…Feel-through tactile interfaces allow for new forms of tactile augmented reality, where real-world objects are superimposed with synthetic tactile renderings (Withana et al, 2018). Integrating touch sensors into deformable surfaces such as textiles (Orth et al, 1998), elastic polymers (Wessely et al, 2016;Teyssier et al, 2020) and even human skin (Weigel et al, 2015;Nittala et al, 2018) has enabled more expressive touch interaction. Emergent technologies are being developed to enrich digital social touch interactions and embed other input modalities such as force, shear, twist, and squeeze (Weigel et al, 2014).…”
Section: Touch Technologymentioning
confidence: 99%
“…First of all, the softer tactility of robot skin can provide host cobots with a better physical interface in affective HRI, compared with traditional rigid components [52]. Tactile information detected by robot skin can not only increase immersion and sense of presence but also convey various pro-social emotions [53]. For example, a stroke, a poke, or a soft push may convey comfort, anger, or calmness, respectively [52], [54].…”
Section: ) Natural Interfaces For Affective Interactionmentioning
confidence: 99%
“…For example, a stroke, a poke, or a soft push may convey comfort, anger, or calmness, respectively [52], [54]. In addition to enabling cobots to recognize human emotions by touch sensing, robot skin can help host cobots directly producing realistic touch to convey their emotions that would be perceived and interpreted by humans, enriching the affective experience [53]. On top of that, the incorporation of various actuators into robot skin, such as thermal, vibrotactile, and stiffness-modulation actuators, provides cobots with the advanced functionality of affective tactile stimulation [35].…”
Section: ) Natural Interfaces For Affective Interactionmentioning
confidence: 99%